How Coretax System User Experience and Digital Tax Literacy Affect Voluntary Tax Compliance Among Generation Z Taxpayers - I Gusti Putu Eka Rustiana Dewi; I Kadek Bagiana (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Indonesia's persistently low tax-to-GDP ratio and the turbulent rollout of the Coretax system in 2025 have raised urgent questions about what drives voluntary tax compliance among Generation Z taxpayers, the country's largest generational cohort. This study investigates the effect of Coretax system user experience and digital tax literacy on voluntary tax compliance among Generation Z taxpayers in Indonesia. A quantitative causality design was employed, with primary data collected through a structured five-point Likert scale questionnaire distributed to Generation Z taxpayers located in Denpasar, Bali, holding an active NPWP and having used Coretax at least once. Data were analysed using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results confirm that both Coretax system user experience and digital tax literacy have a positive and significant effect on voluntary tax compliance. These findings suggest that improving system usability and strengthening digital tax literacy are equally critical strategies for enhancing voluntary compliance among Indonesia's youngest taxpayer generation.